Effect of gibberellic acid on growth and flowering attributes of African marigold (Tagetes erecta) in inner terai of Nepal - Acharya, Samjhana; Ghimire, Bijay; Gaihre, Suraj; Aryal, Krishna; Chhetri, Lal Bahadur (Journal of Agriculture and Natural Resources, 2021)
A field experiment was conducted at Bangaun, Lamahi-3, Dang, Nepal to study the effect of GA3 on growth and flowering attributes of African marigold (Tagetes erecta) in Inner Terai of Nepal. The experiment consists of three replications and 8 treatments and laid out in a randomized complete block design- consisting of various concentrations of GA3 viz. 0ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, and 350ppm. Kolkata local variety of African marigold was tested. The study revealed that among different concentrations of GA3, 300ppm showed the tallest plant height (72.93cm) and the highest basal diameter (1.49cm). Maximum numbers of primary branches (3.11) and the greatest plant spread (32.11cm) were obtained from 250ppm; similarly, maximum numbers of secondary branches (13.80) were recorded in 350ppm. In the case of floral parameters both 100ppm and 350ppm recorded earlier days to 50% flowering (44.00 days each), days for 100% flowering was recorded almost similar in every treatment that sticks around 54 and 55 days, maximum diameter (5.370cm) of flowers were obtained from 50ppm, the greatest fresh weight (6.180g) was recorded in 350ppm, 250ppm showed a maximum number of flower per plant (104.13), similarly, a longer duration of flowering (58 days) was recorded in 300ppm. Among all treatments, the 250ppm level of GA3 was found to be most suitable in terms of production perspective.